2010
DOI: 10.1016/j.juro.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Children With Voiding Problems and Their Parents

Abstract: Results reveal an association between overactive bladder symptoms in children and their parents. To a lesser extent this finding also holds true for dysfunctional voiding symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
2
5
0
1
Order By: Relevance
“…In contrast, Toktamis et al [30] showed that LUTS were significantly more frequent in children with parental history of LUTD during childhood. A recent study reported that mothers of children diagnosed with LUTD had significantly more similar complaints during their childhood [31]. In our study, compared to parents of children without LUTD, significantly more mothers of children with LUTD reported prior history of daily wetting.…”
Section: Discussionsupporting
confidence: 43%
“…In contrast, Toktamis et al [30] showed that LUTS were significantly more frequent in children with parental history of LUTD during childhood. A recent study reported that mothers of children diagnosed with LUTD had significantly more similar complaints during their childhood [31]. In our study, compared to parents of children without LUTD, significantly more mothers of children with LUTD reported prior history of daily wetting.…”
Section: Discussionsupporting
confidence: 43%
“…In a study of 2109 racially diverse women (48% white, 18% black, 16% Latina, 16% Asian), LUTS and urinary tract infections (UTIs) in childhood were shown to be significantly correlated with OAB symptoms in adulthood, including micturition frequency (micturition occurs more frequently during waking hours than previously deemed normal), nocturia (interruption of sleep at least once during the night because of the need to urinate) and urgency (sudden, compelling desire to pass urine, which is difficult to defer) . In addition, an association has been demonstrated between OAB in children and symptoms of urgency and urgency UI in their parents, suggesting that children of parents with a history of OAB symptoms (urgency, frequency, urgency incontinence) are at increased risk for having symptoms themselves either through hereditary factors, environmental factors or learned behaviours . The identification of individuals who may be predisposed to adult LUTS may allow earlier initiation of primary and secondary intervention strategies for prevention of symptom development.…”
Section: Bladder Health Across the Lifespanmentioning
confidence: 99%
“…Many scientific publications have confirmed that hereditary factors play an important role in OAB. Labrie et al22 found that children are more likely to present voiding dysfunction, such as OAB if their parents have similar symptoms. In addition, according to Bush et al,23 the severity of OAB symptoms in children is influenced by their parents.…”
mentioning
confidence: 99%